Desiccation of potato haulm with contact herbicides and the final quality of tubers - Da Silva, Paulo; Blumer, Silvia; Zani Coeti, João Pedro; Cesar Barbosa, Gustavo; Maris Inacio, Estela; Andrea Monquero , Patricia (Comunicata Scientiae, 2021)
Desiccation of potato (Solanum tuberosum L.) haulms makes it possible to establish a physiological homogeneity of the haulms and anticipate the harvest of the tubers. This study aimed to evaluate the efficiency of different herbicides in the desiccation of potato haulms applied at the maturation phenological stages, and the effect of these treatments on the quality of tubers. An experiment was conducted in the field, in an area planted with Orchestra potatoes. This was a completely randomized experimental design with four repetitions. At the maturation phenological stages, the crop was applied with herbicides: diquat dibromide (400 g ha-1), paraquat dichloride (400 g ha-1), saflufenacil (70 g ha-1) and carfentrazone ethyl (60 g ha-1). Visual phytotoxicity assessments were performed at 3, 5, 10 and 15 days after application of treatments (DAT). At 15 DAT, tubers were harvested and evaluated for Brix (%), individual weight (g); diameter (cm); texture (kg/cm2) and starch. At 15 DAT, all herbicides resulted in desiccation close to 100%, however, saflufenacil showed the lowest speed of desiccation, since at 5 DAT the phytotoxicity was less than 86.25%. Texture, brix and diameter showed no statistical difference. The control and saflufenacil resulted in the lowest concentration of starch in the tubers and the highest concentration was obtained for carfentrazone-ethyl, paraquat and diquat. The treatments carfentrazone-ethyl, diquat dibromide and paraquat dichloride, were the most suitable for desiccation of potato haulms, providing fast desiccation speed and greater accumulation of starch in the tubers.